Combined energy production systems with Stirling engines: Analysis of global experience and local prospects - Nikitin, Yevhen (Technologies and Engineering, 2025)
The study aimed to identify the potential of combined energy production systems with Stirling engines by analysing international experience and assessing the prospects for their adaptation to local conditions. The study used an analytical approach to examine global experience, technical solutions, and conditions for the local implementation of combined energy systems based on Stirling engines. The study analysed global experience in the use of Stirling engines in combined energy systems in Europe (the Netherlands, Germany, the United Kingdom), Asia (Japan), and North America (using the example of the National Aeronautics and Space Administration), where they have demonstrated high energy efficiency and environmental friendliness. The results confirmed the possibility of effective application of these systems in Ukraine for decentralised energy supply using local resources. It has been determined that Stirling engines can be effective for decentralised energy supply to rural communities, medical institutions, educational institutions, and critical infrastructure facilities, especially in regions with access to biomass or household waste. It was established that the main barriers remain the high cost of equipment (from EUR 10,000 to EUR 13,000) and the lack of a production base. The payback period for such systems is 6 to 9 years, with annual energy savings of EUR 500-900. It was concluded that, with appropriate state support and localisation of production, combined systems based on Stirling engines have the potential for widespread use as part of a strategy for energy decentralisation and the transition to sustainable energy. In addition, the engines have a service life of 40,000 to 60,000 hours, and maintenance costs range from EUR 100 to EUR 200 per year. The study provided well-founded technical and economic conclusions on the possibility of adapting and implementing combined systems with Stirling engines in local energy conditions, which can serve as a basis for decision-making in the field of sustainable energy